Homeschooling, Civics, and Socialization: The Case of Israel. Issue 7 (September 2019) - Pearlman-Avnion, Shiri; Grayevsky, Mor
The present study uses qualitative and quantitative methods to examine whether homeschooled youth in the largely urbanized social context of Israel differ in their level of civic engagement and social self-efficacy from that of their peers educated at school. Participants completed quantitative questionnaires on civic engagement and social self-efficacy and two personal questionnaires, one quantitative and one qualitative, pertaining to their opinions on various modes of education. No significant differences were found between the degree of civic engagement and sense of social self-efficacy among the two groups. However, within the homeschooling group, social self-efficacy decreased as the number of years they were schooled at home increased, indicating potential negative impact of extended homeschooling. The qualitative study gives insights into attitudes of youth from both groups regarding various modes of education. The findings are discussed in the context of the ongoing debate regarding the pros and cons of homeschooling.